Flight behavior of targeted fishes depends on variables other than fishing. (January 2019) - Stamoulis, Kostantinos A.; Harvey, Euan S.; Friedlander, Alan M.; Williams, Ivor D.; Weng, Kevin C.; Wiggins, Chad; Wagner, Gary W.; Conklin, Eric J.
Highlights: Approach starting distance explained most variability in measures of fish wariness. Other key variables were fish body length, activity, and water depth. Effect sizes of key variables were large in comparison to fishing. New direct measure of minimum approach distance was shorter in the marine reserve. Flight initiation distance did not differ between reserve and fished areas. Abstract: Behavioral changes due to human predation can affect the functional role of targeted fishes and has implications for ecosystem and fisheries management. Wariness of targeted fishes towards divers, often measured as flight initiation distance (FID), has been shown to increase in areas where spear fishing pressure is higher. Additional research is required to understand how these patterns vary among different species and places. To support such studies, there is a need to explore the relationship of approach starting distance (SD) and other variables that influence measures of fish wariness. We used stereo video to record FID, a new direct measure of minimum approach distance (dMAD), and escape responses of targeted reef fishes in a marine reserve and heavily fished area in Hawai'i. We investigated the role of SD and 15 other variables in influencing FID and dMAD and tested differences between the reserve and fished area. SD explained a large portion of the variability in FID and somewhat less variability in dMAD. FID and dMAD were higher when fishes were travelling (vs feeding), increased with fish body length, and decreased with depth. When including these co-variates in models of FID and dMAD of targeted reef fishes, we found significant differences between study sites for dMAD, though not for FID. We also found differences in escape responses between sites. Based on these results, we recommend using stereo video to conduct measures of dMAD as a complement or alternative to FID, while simultaneously measuring SD and collecting additional data such as escape response. Relative effect sizes of SD and, to a lesser extent, other co-variates were large in comparison to site. Studies that use similar methods and do not control for or incorporate SD may produce biased results with regard to the effects of fishing pressure on flight behavior of targeted fishes.